THE ANALYSIS OF MARKET DISCIPLINE IN INDONESIA’S BANKING INDUSTRY - SE, M. ZAFFIER DEWANGGA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The purpose of this research was to analyze the effect market disciplines in Indonesia’s Banking Industry on specific variables, including Capital Adequacy Ratio (CAR), Return on Asset (ROA), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Foreign Owner (FO), Total Asset (TA), and Disclosure Index (DI). The data used in this study was annual data on 2016 taken from Financial Services Authority and Bank Indonesia. This study used regression cross section analysis with the help of a computer program, Stata version 14.2, as the main software to process the research data.The results showed that some of the independent variables (LDR, TA, DI) are significantly affected the change in the Capital Adequacy Ratio. While the other independent variable (ROA, NPL, FO) doesn’t have any effect on CAR. Therefore the analysis for this variable was being done descriptively. In other words, it can be concluded that not all the independent variable are have effect on CAR. Therefore, Loan to Deposit Ratio (LDR), Total Asset (TA), and Disclosure Index (DI)1 has affected by the CAR variable on Market Discipline in Indonesia’s Banking Industry. Keyword: NPL, CAR, ROA, LDR, Disclosure Index